2021
DOI: 10.1101/2021.11.01.466797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the architecture of cerebrospinal fluid cellular communities in neuroinflammatory diseases

Abstract: Cerebrospinal fluid (CSF) biomarkers are important for multiple sclerosis (MS) diagnosis. Moreover, absent of autopsy or biopsy tissue, CSF is the most relevant source for studying the immune cells involved in MS pathophysiology. Single-cell RNA sequencing (scRNA-seq) provides new opportunities to advance our understanding of disease-associated changes in CSF immune cells. Here, using scRNA-seq data generated from 58 CSF and 10 PBMC samples, we provide an updated atlas of the immune cells present in human CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Deeper gene analysis of the latter showed similarities with homeostatic microglia, 36 -a phenotype likely instructed by the CSF microenvironment and not indicating ontogenetically shared origins. 37 Considering these two examples of the integrative data set's advantages, the aim of this study is su ciently met: It supports the previous ndings and und substantiates them with a higher statistical power.…”
Section: Discussionsupporting
confidence: 77%
“…Deeper gene analysis of the latter showed similarities with homeostatic microglia, 36 -a phenotype likely instructed by the CSF microenvironment and not indicating ontogenetically shared origins. 37 Considering these two examples of the integrative data set's advantages, the aim of this study is su ciently met: It supports the previous ndings and und substantiates them with a higher statistical power.…”
Section: Discussionsupporting
confidence: 77%
“…Next to a reduction of microglia-like cells and the well-known expansion of plasma cells and T cells in the CSF of MS patients, the authors observed a reduction of B and T cells and an increase of myeloid cells of ocrelizumab (anti-CD20) treated progressive MS patients versus therapy-naive relapsing-remitting MS patients [15]. The authors speculate that a CD27 downregulation in plasma cells in ocrelizumab-treated MS patients might mediate the immunomodulatory effect of the therapy [15]. While these studies excel through their transcriptional resolution on a single-cell level, many studies lack methodical validation on the protein levels, although some [11,14] provide flow cytometry verification.…”
Section: Dissecting Immune Responses In Complex Neuroinflammatory Dis...mentioning
confidence: 97%
“…In fact, CSF contains a monocyte subpopulation with a microglia-like phenotype [12][13][14], which is almost exclusive to the CSF [11]. This CSF microglia-like population was found to originate from the bone marrow in a single bone marrow transplant recipient patient [15], in contrast to resident microglia of the CNS, which derive from the yolk sac [16,17]. Transcriptionally CSF T cells show enhanced expression of transcripts associated with migration (CD99), interaction with antigenpresenting cells (APC) (CD83, CD84) and chemokines (CXCL16, CXCR5), while genes associated with naive cell state (SELL), cytokine response (IL2RG), and integrins (ITGAL, VLA4) are reduced in CSF T cells compared to blood T cells [11].…”
Section: Csf-a Unique Immune Tissuementioning
confidence: 99%
See 2 more Smart Citations